Iterative methods for solving the generalized split common null point problem in Hilbert spaces. (3rd May 2020) - Reich, Simeon; Tuyen, Truong Minh
Abstract : We propose and study new iterative methods for solving the generalized split common null point problem in Hilbert spaces.